Teleworking: Some Considerations about the Working Instruments and Payment of Expenses - Sampaio, Catarina; Sousa Machado, Susana (Law, State and Telecommunications Review, 2024)
[Purpose] The purpose of this article is to analyze and reflect on the employer's obligations towards the teleworker, to provide the equipment and systems necessary to carry out the work and to compensate for the additional expenses inherent in the scope of the teleworking regime. [Methodology/] The methodology used is based on the theoretical analysis of doctrine and legislative norms in force in the Portuguese legal system, as well as scientific articles. [Findings] With the generalization of teleworking, some regulatory insufficiencies were uncovered, particularly in terms of making working tools available and compensating the associated costs, generating a lively debate. The legislator's intervention in this matter was crucial, putting an end to some gaps that were felt with the new reality and contributing to greater operability of the teleworking regime.